2017
DOI: 10.3892/mmr.2017.7031
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of TAFI by siRNA inhibits invasion and migration of breast cancer cells

Abstract: Human thrombin activatable fibrinolysis inhibitor (TAFI), also known as carboxypeptidase B2 (CPB2), is a procarboxypeptidase enzyme. The purpose of the present study was to observe the expression of TAFI in breast cancer (BC) and breast cancer cell (BCC) lines and to investigate the effect of TAFI suppression by small interfering (si)RNA gene silencing on invasion and migration of BCC lines. A significant increase in TAFI level was identified by immunohistochemical analysis in BC tissues compared with normal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The other study used siRNA to suppress TAFI expression in BCC lines. This research revealed that lowering TAFI expression can reduce growth, invasion and migration in 2 kinds of BCC cells [10]. According to other ndings, In breast cancer cells, siRNA-catenin enhanced the LHX6-induced inhibition of cell proliferation and invasion [11].…”
Section: Introductionmentioning
confidence: 62%
“…The other study used siRNA to suppress TAFI expression in BCC lines. This research revealed that lowering TAFI expression can reduce growth, invasion and migration in 2 kinds of BCC cells [10]. According to other ndings, In breast cancer cells, siRNA-catenin enhanced the LHX6-induced inhibition of cell proliferation and invasion [11].…”
Section: Introductionmentioning
confidence: 62%
“…Furthermore, tumors with high CPB2 expression have been related to more advanced tumor stages ( Balcik et al, 2011 ). Conversely, it has been reported that downregulation of CPB2 expression by siRNA reduces breast cancer cell proliferation, migration, and invasion ( Yu et al, 2017 ). Contrary to the findings of the above studies, our results showed that low expression of CPB2 may facilitate the appearance of STAS and be relevant to worse PFS in adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%